Silver‐plated polyamide fabrics with high electromagnetic shielding effectiveness performance prepared by in situ reduction of polydopamine and chemical silvering. Issue 47 (17th July 2019) - Lu, Yawen; He, Yin; Li, Yafang; Xue, Jie; Liu, Hao; Cheng, Bowen; Li, Xiaojiu
ABSTRACT: In this article, the silver‐plated polyamide fabrics (SPPAFs) with high electroconductibility and shielding effectiveness were fabricated by using in situ reduction of polydopamine and chemical silvering. The effects of SPPAFs dopamine (C8 H11 O2 N) and silver nitrate (AgNO3 ) concentration on surface resistivity and electromagnetic interference shielding effectiveness were studied. The results showed that the surface resistivity of SPPAFs can reach a minimum value of 0.06 ± 0.014 Ω cm −1, when C8 H11 O2 N concentration is 4 g L −1 and the AgNO3 concentration is 120 g L −1 . The shielding effectiveness of SPPAFs in the wide frequency range of 10–3000 MHz increases with the increase in the concentration of AgNO3, and increases first and stabilizes afterward with increasing C8 H11 O2 N concentration. When the concentration of C8 H11 O2 N and AgNO3 is 3 and 120 g L −1, respectively, mean shielding effectiveness values in the low‐, medium‐, and high‐frequency bands are 71.3, 73.8, and 76.1 dB, respectively. Moreover, the mean shielding effectiveness values is 83.79 dB in the frequency range of 1.2–2.3 GHz. The dominant shielding mechanism of SPPAFs is the reflected electromagnetic waves and the absorption shielding effectiveness is less than 2 dB. The average electromagnetic shielding values of SPPAFs are above 67 dB after 16 weeks of storage, when C8 H11 O2 N concentration is 4 g L −1 and the AgNO3 concentration is 80 and 100 g L −1 . The prepared SPPAFs show promising applications in military textiles and smart wearable clothing. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48227. Abstract : Schematic diagram of the preparation process of SPPAFs.